Defining obesity cut-off points for migrant South Asians. - Laura J Gray (Public Library of Science (PLoS), 2011)
Background Body mass index (BMI) and waist circumference (WC) are used to define cardiovascular and type 2 diabetes risk. We aimed to derive appropriate BMI and WC obesity cut-off points in a migrant South Asian population. Methods 4688 White Europeans and 1333 South Asians resident in the UK aged 40-75 years inclusive were screened for type 2 diabetes. Principal components analysis was used to derive a glycaemia, lipid, and a blood pressure factor. Regression models for each factor, adjusted for age and stratified by sex, were used to identify BMI and WC cut-off points in South Asians that correspond to those defined for White Europeans. Findings For South Asian males, derived BMI obesity cut-off points equivalent to 30.0 kg/m(2) in White Europeans were 22.6 kg/m(2) (95% Confidence Interval (95% CI) 20.7 kg/m(2) to 24.5 kg/m(2)) for the glycaemia factor, 26.0 kg/m(2) (95% CI 24.7 kg/m(2) to 27.3 kg/m(2)) for the lipid factor, and 28.4 kg/m(2) (95% CI 26.5 kg/m(2) to 30.4 kg/m(2)) for the blood pressure factor. For WC, derived cut-off points for South Asian males equivalent to 102 cm in White Europeans were 83.8 cm (95% CI 79.3 cm to 88.2 cm) for the glycaemia factor, 91.4 cm (95% CI 86.9 cm to 95.8 cm) for the lipid factor, and 99.3 cm (95% CI 93.3 cm to 105.2 cm) for the blood pressure factor. Lower ethnicity cut-off points were seen for females for both BMI and WC. Conclusions Substantially lower obesity cut-off points are needed in South Asians to detect an equivalent level of dysglycemia and dyslipidemia as observed in White Europeans. South Asian ethnicity could be considered as a similar level of risk as obesity (in White Europeans) for the development of type 2 diabetes.